Lower Healthcare Costs Associated with the Use of a Single-Pill ARV Regimen in the UK, 2004–2008 - Beck, Eduard J.; Mandalia, Sundhiya; Sangha, Roshni; Youle, Mike; Brettle, Ray; Gompels, Mark; Johnson, Margaret; Pozniak, Anton; Schwenk, Achim; Taylor, Stephen; Walsh, John; Wilkins, Ed; et al. (PloS one, 2012)
Investigate the cost and effects of a single-pill versus two- or three pill first-line antiretroviral combinations in reducing viral load, increasing CD4 counts, and first-line failure rate associated with respective regimens at 6 and 12 months. Patients on first-line TDF+3TC+EFV, TDF+FTC+EFV, Truvada®+EFV or Atripla® between 1996-2008 were identified and viral load and CD4 counts measured at baseline, six and twelve months respectively. Factors that independently predicted treatment failure at six and twelve months were derived using multivariate Cox's proportional hazard regression analyses. Use and cost of hospital services were calculated at six and twelve months respectively. All regimens reduced viral load to below the limit of detection and CD4 counts increased to similar levels at six and twelve months for all treatment regimens. No statistically significant differences were observed for rate of treatment failure at six and twelve months. People on Atripla® generated lower healthcare costs for non-AIDS patients at £5,340 (£5,254 to £5,426) per patient-semester and £9,821 (£9,719 to £9,924) per patient-year that was £1,344 (95%CI £1,222 to £1,465) less per patient-semester and £1,954 (95%CI £1,801 to £2,107) less per patient-year compared with Truvada®+EFV; healthcare costs for AIDS patients were similar across all regimens. The single pill regimen is as effective as the two- and three-pill regimens of the same drugs, but if started as first-line induction therapy there would be a 20% savings on healthcare costs at six and 17% of costs at twelve months compared with Truvada®+EFV, that generated the next lowest costs.